SAFETEL: a pilot randomised controlled trial to assess the feasibility and acceptability of a safety planning and telephone follow-up intervention to reduce suicidal behaviour - Rory C. O’Connor; Susie Smillie; Heather McClelland; Jenna-Marie Lundy; Corinna Stewart; Suzy Syrett; Marcela Gavigan; Alex McConnachie; Bethany Stanley; Michael Smith; Gregory K. Brown; Barbara Stanley; et al. (Pilot and Feasibility Studies, 2022)
Abstract Background A previous suicide attempt is an important predictor of future suicide. However, there are no evidence-based interventions administered in UK general hospital contexts to reduce suicidal behaviour in patients admitted following a suicide attempt. Consequently, the objective of this pilot randomised controlled trial was to explore whether a safety planning and telephone follow-up intervention (SAFETEL) was feasible and acceptable for individuals treated in hospital following a suicide attempt. Methods In this three-phase study with an embedded process evaluation, a safety planning intervention was tailored to the UK context (Phase I), piloted (Phase II, n = 32), and tested in a feasibility randomised controlled trial (Phase III). In Phase III, participants were allocated to either the intervention (n = 80) or control group (n = 40) using telephone randomisation with a 2:1 ratio. The acceptability and feasibility of the trial and intervention procedures were evaluated using both qualitative (interviews and focus groups) and quantitative data. The number of hospital representations of suicidal behaviour was also collected 6 months after study recruitment based on electronic patient records. Results Findings indicated that SAFETEL was both acceptable and feasible. Hospital staff reported the intervention fitted and complemented existing services, and patients reported that they favoured the simplicity and person-centred approach of the safety planning intervention. Conclusions All progression criteria were met supporting further evaluation of the intervention in a full-scale clinical effectiveness trial. Trial registration ISRCT, ISRCTN62181241 , 5/5/2017